Implementasi Media Jejak Penari Pada Pembelajaran Tari Topeng Malang di Kelas VII-C SMPN 10 Malang - Pratiwi, Shella Hardi; Pratamawati, E. W. Suprihatin Dyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Malang Mask Dance, as one of the traditional arts that is full of cultural and historical values, which requires an interesting and interactive learning approach with the aim that students are able to analyze and appreciate it optimally. Critical thinking as the most important ability in the 21st century is also the main focus of this study. This article is used to examine the effectiveness of the dance trail game related to critical thinking skills regarding the main elements and supporting elements of the Malang mask dance. The study used Pre-Experimental with quantitative data collection with subjects choosing class VII-C students of SMPN 10 Malang. Data were obtained through observation and tests with quantitative data obtained through observation to determine students' opinions and experiences during learning with the dance trail game and tests to assess their level of critical thinking skills before and after the implementation of the dance trail game.